Analisis Keefektifan Penggunaan Video Sebagai Media Pembelajaran Ilmu Pengetahuan Alam Pada Siswa Kelas 6 SD Islam Al Ilmu - Abdullah Abdullah; Salmatus Sauda (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The success of students in achieving learning objectives is not only caused by internal factors but also by the intervention of external factors. The current digital era requires teachers to innovate, not just relying on learning that is centered on printed books. One way to utilize digital in learning is by using video media. Natural science is often not very popular with students because the material is extensive and complex, even though this science is important to be studied universally and critically. In addition, there are many obstacles that occur in learning natural science in class. That is what makes teachers use video as a media aid in learning. This study was conducted to analyze the effectiveness of using video as a learning medium, especially in science learning. Analysis of effectiveness using a questionnaire method to determine student responses when learning using additional video media. Can video media produce optimal learning objectives or vice versa. Research data were obtained from the results of a questionnaire distributed to all 6th grade students of SD Islam Al Ilmu. The results of the analysis of the effectiveness of video as a learning medium are that it can be effective to use because it can improve students' understanding of the material, produce active learning, and can motivate students to reflect on knowledge in everyday life.